2017
DOI: 10.1097/mlr.0000000000000737
|View full text |Cite
|
Sign up to set email alerts
|

Coordinating Care Across Health Care Systems for Veterans With Gynecologic Malignancies

Abstract: Experiences in coordinating care for women Veterans with gynecologic malignancies receiving concurrent VA and community cancer care reveal challenges inherent in delivering care across health care systems, as well as potential approaches for addressing them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 46 publications
0
50
0
Order By: Relevance
“…13 Both VA and non-VA providers have reported significant frustration with crosssystem care coordination, particularly related to barriers to information exchange and a lack of role clarity and care tracking. [14][15][16][17] Health information technology (IT) has been shown to be an essential part of effective information exchange, but is itself highly complex and reflects only one component of achieving coordinated care. 18,19…”
Section: Current Evidence On Cross-system Care Coordinationmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Both VA and non-VA providers have reported significant frustration with crosssystem care coordination, particularly related to barriers to information exchange and a lack of role clarity and care tracking. [14][15][16][17] Health information technology (IT) has been shown to be an essential part of effective information exchange, but is itself highly complex and reflects only one component of achieving coordinated care. 18,19…”
Section: Current Evidence On Cross-system Care Coordinationmentioning
confidence: 99%
“…Early research of VCP implementation found that there were communication difficulties among stakeholders (e.g., VHA, third-party administrators, community providers, and patients), slow or incomplete exchange of medical records, network provider shortages, and concurrent barriers to community provider participation. 3,14,17,29,30 The number of providers, providers' distribution across specialties (i.e., health professional shortage areas), locations of existing providers (e.g., clusters in urban vs. rural areas), and provider preferences (e.g., capacity to accept new patients, reimbursement limits) are not necessarily aligned with optimal care and coordination and so need further evaluation. Careful assessment of where current provider networks are inadequate, and for what specialties, will be required to support targeted network development toward the goal of increasing long-term capacity for delivery of community care.…”
Section: Care Coordination Measurement Systemsmentioning
confidence: 99%
“…In particular, increased fragmentation of care may result in additional challenges for coordination and continuity of care provided . The impact of increased care fragmentation is expected to be more pronounced for Veterans with greater health care utilization, and among them women Veterans, who have additional health burdens and complex care needs …”
Section: Introductionmentioning
confidence: 99%
“…3 The impact of increased care fragmentation is expected to be more pronounced for Veterans with greater health care utilization, and among them women Veterans, who have additional health burdens and complex care needs. 4,5 Women Veterans (WVs) constitute the fastest growing segment of VA patients, but represent a numerical minority within VA facilities (<10 percent of VA users). 6 Delivering women's health (WH) services, maintaining provider competencies in WH, and providing gender-sensitive care environments have been challenging for VA facilities traditionally oriented toward the care of male patients.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings provide quantitative support to qualitative studies that have elucidated care coordination challenges by women veterans using non-VA care for some of their health needs. 4,19 However, further attention needs to be given to those veterans with poor integrated care scores, specifically as to whether these veterans have worse health outcomes than veterans with high integration. Furthermore, echoing previous studies, 20 our study also points to the need to ensure non-VA care providers are provided sufficient medical information on women veterans in their care and should underscore efforts for the VA to be more collaborative in its relationships with community providers.…”
Section: Discussionmentioning
confidence: 99%